Theoretical model for damage and vibration response in concrete bridges - Abdul Rahman, Azlan; Ahmad, Baderul Hisham; Bakri, Ahmadon; Yong, Chou Yu (Faculty of Civil Engineering, 2009)
The use of vibration signatures for structural health monitoring (SHM) purposes has been used in various fields, such as mechanical and aerospace engineering for many years. In recent years, its potential for use with civil engineering structures has been investigated and of particular interest in civil engineering is its applicability to buildings and bridges. It is recently known that each structure has its typical dynamic behaviour, which may be addressed as vibrational signature. Any changes in a structure, such as all kinds of damages and deteriorations leading to decrease of the load-carrying capacity have an impact on dynamic response, hence suggesting the use of dynamic response characteristics for the evaluation of quality and structural integrity. Monitoring of the dynamic response of structures makes it possible to get very quick knowledge of the actual conditions and helps in planning of rehabilitation budgets. One of the promising developments in structural vibration monitoring is the ambient vibration testing which does not require a controlled excitation of the structure. The structural response to ambient excitation can be recorded in large number of points and from these ambient measurement, the condition of the structure can be derived. A classification of the structures can be developed based on vibration monitoring using the modal parameters natural frequencies, mode shapes, damping values and vibration intensities. The ambient vibration testing represents a real operating condition of the structure. This report presents a theoretical and experimental ambient modal analysis on three existing structures namely a staircase, a timber footbridge and a concrete bridge. The field-testing has provided opportunity to analyse dynamic properties of the three selected structures. The operational modal analysis software, ARTeMIS Extractor is a tool used for analysing the raw data to obtain the dynamic properties of the structures. Finite element modelling and analysis on the structure by using finite element software, ANSYS were developed. The comparison between the mode shapes determined from both analyses showed some similarity. The natural frequencies that were generated had a variance between the two analyses. Thus, the modal updating is essential on the next stage. Improvement in the field-testing is needed in order to obtain more accurate and quality results. Overall, modal analysis is comparable as an alternative to extract dynamic properties of the structures.